Code Mixing on Quipper Youtube Channel: A Sociolinguistics Study - Muhammad Saibani Wiyanto (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
People in Indonesia often use two languages interchangeably or by mixing two language conversations in daily life. The phenomenon of mixing language is often called code mixing. Code mixing also used on Quipper video, the speaker submits learning material using code mixing to make it easier to understand. The purpose of this study is to find out the types of code mixing by Hoffman's theory namely intra-sentential code mixing, intra-lexical code mixing, and involving a change of pronunciation, and the factors that influence code mixing by Holmes's theory namely the participants, social context, the topic, and the function. This study used qualitative content analysis as an approach. The data source will take from Quipper video Indonesia Youtube channel. The results of this study showed that the teacher used all the types of code mixing by Hoffman namely intra-sentential code mixing 87%, intra-lexical code mixing 11%, and involving a change of pronunciation 2%. While for the factors that influence code mixing, the researcher found three factors that used by the teacher namely the participants 30%, the topic 45%, and the function 25%.